Financial literacy learning through socio-drama of buying and selling - Prodyanatasari, Arshy (Journal of Community Service in Science and Engineering (JoCSE), 2025)
Financial literacy is a critical life skill that needs to be introduced from an early age. This community engagement activity aimed to enhance elementary school students’ understanding of money management through an engaging, participatory approach. The program was conducted in March 2024 at SDN Bujel 3, Kediri City, involving 43 student participants. The primary objectives were to develop students’ comprehension of the value of money, improve their transaction-related skills, and strengthen their basic financial calculation abilities. The method used was Participatory Action Research (PAR), employing a socio-drama approach centered around buying and selling scenarios. This interactive method enabled students to role-play as buyers and sellers, thus learning practical financial concepts in a realistic and enjoyable context. The activity also fostered students’ negotiation skills and social interaction. Evaluation was carried out through a comparison of pre-test and post-test scores, analyzed using the Wilcoxon Nonparametric Statistical Test due to the non-normal distribution of the data. The results indicated a statistically significant improvement in students’ financial literacy, particularly in terms of understanding money value, arithmetic calculations, and transaction management. Furthermore, students displayed increased confidence and improved social interaction skills. In conclusion, the integration of socio-drama in financial literacy education proved effective in fostering not only cognitive understanding but also essential life skills in elementary school students. This method presents a promising alternative approach for future financial literacy programs in primary education settings.Literasi keuangan merupakan keterampilan hidup penting yang perlu diperkenalkan sejak usia dini. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pemahaman siswa sekolah dasar tentang pengelolaan uang melalui pendekatan partisipatif yang menarik. Program ini dilaksanakan pada bulan Maret 2024 di SDN Bujel 3, Kota Kediri, dengan melibatkan 43 peserta siswa. Tujuan utamanya adalah untuk mengembangkan pemahaman siswa tentang nilai uang, meningkatkan keterampilan terkait transaksi, dan memperkuat kemampuan perhitungan keuangan dasar mereka. Metode yang digunakan adalah Participatory Action Research (PAR), dengan menggunakan pendekatan sosiodrama yang berpusat pada skenario jual beli. Metode interaktif ini memungkinkan siswa untuk bermain peran sebagai pembeli dan penjual, sehingga mempelajari konsep keuangan praktis dalam konteks yang realistis dan menyenangkan. Kegiatan ini juga menumbuhkan keterampilan negosiasi dan interaksi sosial siswa. Evaluasi dilakukan melalui perbandingan skor pra-tes dan pasca-tes, dianalisis menggunakan Uji Statistik Nonparametrik Wilcoxon karena distribusi data yang tidak normal. Hasilnya menunjukkan peningkatan yang signifikan secara statistik dalam literasi keuangan siswa, khususnya dalam hal pemahaman nilai uang, perhitungan aritmatika, dan manajemen transaksi. Lebih jauh lagi, siswa menunjukkan peningkatan kepercayaan diri dan peningkatan keterampilan interaksi sosial. Sebagai kesimpulan, integrasi sosiodrama dalam pendidikan literasi keuangan terbukti efektif dalam menumbuhkan tidak hanya pemahaman kognitif tetapi juga keterampilan hidup yang penting pada siswa sekolah dasar. Metode ini menyajikan pendekatan alternatif yang menjanjikan untuk program literasi keuangan di masa mendatang dalam lingkungan pendidikan dasar.